Integrated single cell analysis of blood and cerebrospinal fluid leukocytes in multiple sclerosis - Schafflick, David; Xu, Chenling A.; Hartlehnert, Maike; Cole, Michael; Schulte-Mecklenbeck, Andreas; Lautwein, Tobias; Wolbert, Jolien; Heming, Michael; Meuth, Sven G.; Kuhlmann, Tanja; Gross, Catharina C.; Wiendl, Heinz; et al. (Nature communications, 2020)
Cerebrospinal fluid (CSF) protects the central nervous system (CNS) and analyzing CSF aids the diagnosis of CNS diseases, but our understanding of CSF leukocytes remains superficial. Here, using single cell transcriptomics, we identify a specific location-associated composition and transcriptome of CSF leukocytes. Multiple sclerosis (MS) – an autoimmune disease of the CNS – increases transcriptional diversity in blood, but increases cell type diversity in CSF including a higher abundance of cytotoxic phenotype T helper cells. An analytical approach, named cell set enrichment analysis (CSEA) identifies a cluster-independent increase of follicular (TFH) cells potentially driving the known expansion of B lineage cells in the CSF in MS. In mice, TFH cells accordingly promote B cell infiltration into the CNS and the severity of MS animal models. Immune mechanisms in MS are thus highly compartmentalized and indicate ongoing local T/B cell interaction. Here the authors provide a single-cell characterization of cerebrospinal fluid and blood of newly diagnosed multiple sclerosis (MS) patients, revealing altered composition of lymphocyte and monocyte subsets, validated by other methods including the interrogation of the TFH subset in mouse models of MS.